The role of protein acetylation in regulating mitochondrial fusion and fission. (17th December 2021) - Uddin, Golam M.; Abbas, Rafa; Shutt, Timothy E.
Abstract : The dynamic processes of mitochondrial fusion and fission determine the shape of mitochondria, which can range from individual fragments to a hyperfused network, and influence mitochondrial function. Changes in mitochondrial shape can occur rapidly, allowing mitochondria to adapt to specific cues and changing cellular demands. Here, we will review what is known about how key proteins required for mitochondrial fusion and fission are regulated by their acetylation status, with acetylation promoting fission and deacetylation enhancing fusion. In particular, we will examine the roles of NAD + dependant sirtuin deacetylases, which mediate mitochondrial acetylation, and how this post-translational modification provides an exquisite regulatory mechanism to co-ordinate mitochondrial function with metabolic demands of the cell.